?iwa-Buddha doctrine implementation in clergy symbol towards Hindu society at Lombok - Mustika, I Ketut Cameng (International research journal of management, IT and social sciences, 2017)
The present research was intended to reveal ?iwa-Buddha doctrine implementation in the clergy symbol domain toward Hindu religious society at Lombok. Regarding the research was focused on the background, functions, and meanings of ?iwa-Buddha doctrine implementation in the clergy symbol to Hindu society at Lombok. An existence background of ?iwa-Buddha doctrine included the three. First, ?iwa-Buddha doctrines influence was from Majapahit kingdom period. Second, ?iwa-Buddha doctrines were diffused by Balinese people during Dalem Waturenggong period at the Gelgel Kingdom. Third, the large deployment was during Karangasem kingdom expanded territory in Lombok. ?iwa-Buddha doctrine was implemented in the clergy symbol domain had occurred before both doctrines entry Lombok island. ?iwa-Buddha function doctrines in the religious symbols towards Hindu society at Lombok, related to the fundamentally functions that was used as a basis for the individually and collectively doctrines religion realization. The functions of the ?iwa-Buddha doctrines implementation in the religious symbols towards Hindu society at Lombok included: philosophies system integration between ?iwa and Buddhism doctrines, realizing social integrity between adherents of ?iwa and Buddhists, and improving religious consciousness in divinity aspect of living.